Vitamin B12 absorption in some neurological and neuroendocrine disorders. Issue 7 (October 1970) - Donaldson, D.; Lascelles, P. T.
Abstract : An assessment of vitamin B12 absorption in neurological patients has been made by both serum and urine counting of 57 Co cyanocobalamin during the conventional Schilling test. Although patients with pernicious anaemia, some with subacute combined degeneration of the cord, have been studied, emphasis in the discussion is placed on the significantly increased excretion of the radioactive vitamin in a group of patients with pituitary insufficiency. Results are also given for epileptic patients who have developed folate deficiency (as assessed by serum folate levels) coincidental with anticonvulsant therapy, as well as for some patients who have had neurological symptoms or signs following partial gastrectomy operations.